2011
DOI: 10.1177/2040622311399145
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction with aging and the role of inflammation

Abstract: As the average lifespan continues to climb because of advances in medical care, there is a greater need to understand the factors that contribute to quality of life in the elderly. The capacity to live independently is highly significant in this regard, but is compromised by cognitive dysfunction. Aging is associated with decreases in cognitive function, including impairments in episodic memory and executive functioning. The prefrontal cortex appears to be particularly vulnerable to the effects of advancing ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
155
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(155 citation statements)
references
References 214 publications
(267 reference statements)
0
155
0
Order By: Relevance
“…The balancing and stress-reducing effects of MM may positively influence ageing by improving functioning of ANS ), HPA axis and immune functions (Creswell et al 2012;Epel et al 2009;Epel et al 2013;Larouche et al 2015). As all three factors have been implicated in decline of brain structure (Frewen et al 2013;Larouche et al 2015;Lupien et al 2009;McEwen and Magarinos 2001;Simen et al 2011), the brain state training of MM may also enhance neural reserve via this indirect pathway.…”
Section: Ageing Lifestyle and Cognitive Reservementioning
confidence: 99%
“…The balancing and stress-reducing effects of MM may positively influence ageing by improving functioning of ANS ), HPA axis and immune functions (Creswell et al 2012;Epel et al 2009;Epel et al 2013;Larouche et al 2015). As all three factors have been implicated in decline of brain structure (Frewen et al 2013;Larouche et al 2015;Lupien et al 2009;McEwen and Magarinos 2001;Simen et al 2011), the brain state training of MM may also enhance neural reserve via this indirect pathway.…”
Section: Ageing Lifestyle and Cognitive Reservementioning
confidence: 99%
“…First, we cannot determine causality, because this study was cross-sectional. However, prior studies have provided evidence that inflammation has a role in the progression of cognitive impairment [46,47]. These findings give us confidence that inflammation influences cognition during HAND, rather than the reverse.…”
Section: Discussionmentioning
confidence: 67%
“…Additionally, prolonged allograft ischemic time has been associated with impaired gas exchange (i.e., Pa O 2 /FI O 2 ) immediately postoperatively (34) and impaired longterm survival. Confirmatory studies, designed to examine markers of oxidative stress (34,35), inflammation (e.g., IL-18) (35,(43)(44)(45), and oxygenation postoperatively as potential mediators of the observed relationships between allograft ischemic time, oxygenation, and cognitive function, are required to validate our observations. Related future studies are required to examine whether the previously identified relationship between prolonged allograft ischemic time and long-term survival (34) is mediated by cognitive impairment and the potential adverse events related to such impairment (i.e., functional impairment, medication nonadherence, infectious complications) (46,47).…”
Section: Original Researchmentioning
confidence: 85%
“…We had proposed that allograft ischemic time may result in cognitive decline due to systemic effects of ischemia-reperfusion injury, mediated by oxidative stress and inflammation, which could lead to neuroinflammation (34,35,43,44). Additionally, prolonged allograft ischemic time has been associated with impaired gas exchange (i.e., Pa O 2 /FI O 2 ) immediately postoperatively (34) and impaired longterm survival.…”
Section: Original Researchmentioning
confidence: 99%